Tissue factor procoagulant activity of plasma microparticles is increased in patients with early-stage prostate cancer - Haubold, Katja; Rink, Michael; Spath, Brigitte; Friedrich, Martin; Chun, Felix Kyoung-Hwan; Marx, Guy; Amirkhosravi, Ali; Francis, John L.; Bokemeyer, Carsten; Eifrig, Barbara; Langer, Florian (Thrombosis and Haemostasis, 2009)
Tissue factor (TF) plays a critical role in tumour growth and metastasis, and its enhanced release into plasma in association with cellular microparticles (MPs) has recently been associated with pathological cancer progression. We have previously demonstrated significantly elevated levels of plasma TF antigen as well as systemic coagulation and platelet activation in patients with localised prostate cancer. In this prospective study, we used a highly sensitive one-stage clotting assay to measure preoperative TF-specific procoagulant activity (PCA) of plasma MPs in 68 consecutive patients with early-stage prostate cancer to further explore the relevance of circulating TF in this tumour entity. Automated calibrated thrombography was used to monitor thrombin generation in cell-free plasma samples in the absence of exogenous TF or phospholipids. Compared to healthy male controls (n=20), patients had significantly increased levels of both D-dimer and TF-specific PCA of plasma MPs (p<0.001). Furthermore, MP-associated TF PCA was higher in patients with (n=29) than in those without (n=39) laboratory evidence of an acute-phase reaction (p=0.004) and decreased to normal levels within one week after radical prostatectomy. Overall, we found a significant correlation between TF-specific PCA of plasma MPs and plasma D-dimer (p=0.002), suggesting that plasma MPs contributed to in-vivo coagulation activation in a TF-dependent manner. Thrombin generation in plasma was also significantly increased in patients compared to controls (p<0.01). Collectively, our findings suggest that TF-specific PCA of plasma MPs contributes to intravascular coagulation activation in patients with early-stage prostate cancer and may represent a potential link between hypercoagulability, inflammation, and disease progression.
Keywords: Microparticles; tissue factor / factor VIIa; cancer